(untitled) (Journal of the College of Basic Education, 2023)
In this research, commonly used aluminum utensils were selected from the local marketsIn which distilled water was boiled and ions removed from it, and other utensils where distilled water was boiledFrom which ions are removed, citric acid is added to it at a rate of 1 g / 2500 ml for several times.ranged from 15 to 90 minutes; Then the percentage and quantity of some mineral elements were measured.The obtained results showed the presence of a number of metallic elements in the boiled liquidIn the aluminum utensils under study, to which citric acid was added, while the liquid that was left was clearedIt was boiled with pyrex pots of metal elements; It also showed an increase in proportionsThe presence of metallic elements that were detected by increasing the heating period with the presence of acidThey are iron, copper, cadmium and aluminum, but all samples were devoid of any elementLead.